Multidrug-Resistant Enteropathogenic Escherichia coli Isolated from Diarrhoeic Calves, Milk, and Workers in Dairy Farms: A Potential Public Health Risk - Ibrahim E. Eldesoukey; Walid Elmonir; Abdulaziz Alouffi; Eman I. M. Beleta; Mohamed A. Kelany; Shimaa Samir Elnahriry; Mohammed Ibrahim Alghonaim; Zeyad Abdullah alZeyadi; Haitham Elaadli (MDPI AG, 2022)
Enteropathogenic Escherichia coli (EPEC) is a leading cause of diarrhoeagenic diseases in humans and cattle worldwide. The emergence of multidrug-resistant (MDR) EPEC from cattle sources is a public health concern. A total of 240 samples (75 diarrhoeic calves, 150 milk samples, and 15 workers) were examined for prevalence of EPEC in three dairy farms in Egypt. Antimicrobial resistance (AMR) traits were determined by antibiogram and polymerase chain reaction (PCR) detection of β-lactamase-encoding genes, plasmid-mediated quinolone resistance genes, and carbapenemase-encoding genes. The genetic relatedness of the isolates was assessed using repetitive extragenic palindromic sequence-based PCR (REP-PCR). EPEC isolates were detected in 22.7% (17/75) of diarrhoeic calves, 5.3% (8/150) of milk samples, and 20% (3/15) of worker samples. The detected serovars were O26 (5%), O111 (3.3%), O124 (1.6%), O126 (0.8%), and O55 (0.8%). AMR-EPEC (harbouring any AMR gene) was detected in 9.2% of samples. Among isolates, blaTEM was the most detected gene (39.3%), followed by blaSHV (32.1%) and blaCTX-M-1 (25%). The qnrA, qnrB, and qnrS genes were detected in 21.4%, 10.7%, and 7.1% of isolates, respectively. The blaVIM gene was detected in 14.3% of isolates. All EPEC (100%) isolates were MDR. High resistance rates were reported for ampicillin (100%), tetracycline (89.3%), cefazolin (71%), and ciprofloxacin (64.3%). Three O26 isolates and two O111 isolates showed the highest multiple-antibiotic resistance (MAR) indices (0.85-0.92); these isolates harboured blaSHV-12 and blaCTX-M-15 genes, respectively. REP-PCR genotyping showed high genetic diversity of EPEC, although isolates belonging to the same serotype or farm were clustered together. Two worker isolates (O111 and O26) showed high genetic similarity (80-95%) with diarrhoeic calf isolates of matched serotypes/farms. This may highlight potential inter-species transmission within the farm. This study highlights the potential high risk of cattle (especially diarrhoeic calves) as disseminators of MDR-EPEC and/or their AMR genes in the study area. Prohibition of non-prescribed use of antibiotics in dairy farms in Egypt is strongly warranted.